Ernesto : the untold story of Hemingway in revolutionary Cuba - Feldman, Andrew, 1973- (Melville House, 2019)
"Ernest Hemingway first visited Cuba in 1928, and the experience would change the course of his entire life. He settled in Cojimar--a tiny fishing village east of Havana--in 1940, and came to think of himself as Cuban. What he discovered there, a new world counterpart to his beloved Spain, provided him the material for the novel that would rescue his uncertain career. The Old Man and the Sea won him a Pulitzer Prize and, one year later, earned literature's highest honor--the Nobel Prize. Recognizing his debt, Hemingway announced to the press that he had won the prize "as a citizen of Cojimar." This is the Hemingway story that has never been told: the full story of Papa as an expatriate in Cuba, an ingenuous American opportunist whose natural openness and curiosity connected with the distinctive warmth of the Cuban character. In Cuba he formed key artistic relationships -- including a longstanding affair with a previously undiscovered Cuban lover, Leopoldina Roderiguez -- and became the Nobel Prize-winning literary legend we know today"--